Assessing the role of circular economy and green innovation in mitigating carbon emissions in the Visegrad countries - Takyi, Kwabena Nsiah; Gavurova, Beata; Charles, Ofori; Mikeska, Martin; Sampene, Agyemang Kwasi (International Journal of Renewable Energy Development, 2024)
The shift towards a circular economy is an essential measure in achieving sustainable development because it seeks to separate economic expansion from resource use and environmental deterioration. To meet the European Union green deal, waste management, and the net zero emissions targets various countries are developing and adopting prudent strategies. This study investigates the dynamic affiliation between circular economy (CIR), green innovation (INV), renewable energy (REE), economic progress (GDP), and urbanisation (URB) on carbon emissions (CO2) in the Visegrad (V4) countries, comprising the Czech Republic, Hungary, Poland, and Slovakia. Using the CS-ARDL technique and quantile regression, data curation from 1990-2022 was analysed after checking for cross-sectional, unit root, and cointegration. The outcome demonstrates that circular economy, green innovation, and renewable energy had a negative effect on carbon emissions. In addition, GDP and URB had an immaterially positive influence on carbon emissions. Lastly, the quantile regression confirmed that the study provides useful information for policymakers and stakeholders in the Visegrad countries. It emphasised how important it is to take a broad approach to circular economy initiatives, support eco-friendly innovations, carry out renewable energy projects, and manage the urbanisation process well to achieve long-term economic growth and environmental health.